(untitled) (Research, Society and Development, 2021)
Due to the need for rehabilitation with dental implants, maxillary sinus lifting surgery is described as a safe technique, in this case report we demonstrate a modified maxillary sinus lifting technique, the pillow technique, in which a pillow is made with a absorbable membrane filled with bone graft. At the time of surgery, the side window technique with displacement of the Schneider membrane and insertion of the pillow is used. As a clinical result, a satisfactory amount of bone gain was observed in the 11-month postoperative period. With this technique, it is possible to obtain a shorter surgical time due to the need only for the preparation of the receiving bed, since the pillow is made prior to the surgical act, in addition to a new maneuver for the protection of the biomaterial in cases of perforations of the Schneider membrane decreasing the chance of postoperative complications.